-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathchapter9-3-plus-comm.rkt
204 lines (162 loc) · 4.77 KB
/
chapter9-3-plus-comm.rkt
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
#lang pie
;; Define a function called plus-comm that states and proves that
;; + is commutative
;;
;; (claim plus-comm
;; (Pi ((n Nat) (m Nat))
;; (= Nat (+ n m) (+ m n))))
;;
;; Bonus: Write the solution using the trans eliminator instead of
;; the replace elimiator.
;; https://docs.racket-lang.org/pie/index.html#%28def._%28%28lib._pie%2Fmain..rkt%29._trans%29%29
;;
;; (trans target-1 target-2) -> (= X from to)
;; target-1 : (= X from middle)
;; target-2 : (= X middle to)
(claim + (-> Nat Nat Nat))
(define +
(lambda (a b)
(rec-Nat a
b
(lambda (_ b+a-1)
(add1 b+a-1)))))
;; prove 0 + n = n + 0
(claim mot-zero+=+zero
(-> Nat U))
(define mot-zero+=+zero
(lambda (n)
(= Nat (+ 0 n) (+ n 0))))
(claim step-zero+=+zero
(Pi ((n-1 Nat))
(-> (= Nat (+ 0 n-1) (+ n-1 0))
(= Nat (+ 0 (add1 n-1)) (+ (add1 n-1) 0)))))
(define step-zero+=+zero
(lambda (n-1)
(lambda (zero+n-1=n-1+zero)
(cong zero+n-1=n-1+zero (+ 1)))))
(claim zero+=+zero
(Pi ((n Nat))
(= Nat (+ 0 n) (+ n 0))))
(define zero+=+zero
(lambda (n)
(ind-Nat n
mot-zero+=+zero
(same 0)
step-zero+=+zero)))
;; back to plus-comm
(claim mot-plus-comm
(-> Nat Nat U))
(define mot-plus-comm
(lambda (m n)
(= Nat (+ n m) (+ m n))))
;;what the claim for step-plus-comm would look like:
;;(claim step-plus-comm
;; (Pi ((m Nat) (n-1 Nat))
;; (-> (= Nat (+ n-1 m) (+ m n-1))
;; (= Nat (+ (add1 n-1) m) (+ m (add1 n-1))))))
;; because of this fact
(claim n+1+m=1+n+m
(Pi ((m Nat) (n Nat))
(= Nat (+ (add1 n) m) (add1 (+ n m)))))
(define n+1+m=1+n+m
(lambda (m n)
(same (add1 (+ n m)))))
;; this is the same type as step-plus-comm
;; (claim step-plus-comm
;; (Pi ((m Nat) (n-1 Nat))
;; (-> (= Nat (+ n-1 m) (+ m n-1))
;; (= Nat (add1 (+ n-1 m)) (+ m (add1 n-1))))))
;; if we can prove this
(claim n+m+1=1+n+m
(Pi ((m Nat) (n Nat))
(= Nat (+ n (add1 m)) (add1 (+ n m)))))
;; then
;; this is the same type as step-plus-comm
;; (claim step-plus-comm
;; (Pi ((m Nat) (n-1 Nat))
;; (-> (= Nat (+ n-1 m) (+ m n-1))
;; (= Nat (add1 (+ n-1 m)) (add1 (+ m n-1))))))
;; which means we simply need to cong add1
(claim mot-n+m+1=1+n+m
(-> Nat Nat U))
(define mot-n+m+1=1+n+m
(lambda (m n)
(= Nat (+ n (add1 m)) (add1 (+ n m)))))
(claim step-mot-n+m+1=1+n+m
(Pi ((m Nat) (n-1 Nat))
(-> (= Nat (+ n-1 (add1 m)) (add1 (+ n-1 m)))
(= Nat (+ (add1 n-1) (add1 m)) (add1 (+ (add1 n-1) m))))))
(define step-mot-n+m+1=1+n+m
(lambda (m n-1)
(lambda (n-1+m+1=1+n-1+m)
(cong n-1+m+1=1+n-1+m (+ 1)))))
(define n+m+1=1+n+m
(lambda (m n)
(ind-Nat n
(mot-n+m+1=1+n+m m)
(same (add1 m))
(step-mot-n+m+1=1+n+m m)
)))
;; proved n + (add1 m) = add1 (n + m)
;; unfortunately we need to symmetric version
(claim 1+n+m=n+m+1
(Pi ((m Nat) (n-1 Nat))
(= Nat (add1 (+ m n-1)) (+ m (add1 n-1)))))
(define 1+n+m=n+m+1
(lambda (m n-1)
(symm (n+m+1=1+n+m n-1 m))))
;; now we have everything we need to complete step-plus-comm
(claim step-plus-comm
(Pi ((m Nat) (n-1 Nat))
(-> (= Nat (+ n-1 m) (+ m n-1))
(= Nat (+ (add1 n-1) m) (+ m (add1 n-1))))))
;; so now we get to this, the fact n+1+m=1+n+m and the proof 1+n+m=n+m+1
;; (claim step-plus-comm
;; (Pi ((m Nat) (n-1 Nat))
;; (-> (= Nat (+ n-1 m) (+ m n-1))
;; (= Nat (add1 (+ n-1 m)) (add1 (+ m n-1))))))
;; push-add1 will push the add1 down to n-1
(claim push-add1
(Pi ((n-1 Nat) (m Nat))
(->
(= Nat (add1 (+ n-1 m)) (add1 (+ m n-1)))
(= Nat (+ (add1 n-1) m) (+ m (add1 n-1))))))
;; here is the main proof we are going to need
;; (= Nat (add1 (+ m n-1)) (+ m (add1 n-1)))
(define push-add1
(lambda (n-1 m)
(lambda (1+n-1+m=1+m+n-1)
(replace (1+n+m=n+m+1 m n-1)
(lambda (toreplace) (= Nat (add1 (+ n-1 m)) toreplace))
1+n-1+m=1+m+n-1))))
;; an alternative implementation of push-add1 using trans
(claim push-add1-trans
(Pi ((n-1 Nat) (m Nat))
(->
(= Nat (add1 (+ n-1 m)) (add1 (+ m n-1)))
(= Nat (+ (add1 n-1) m) (+ m (add1 n-1))))))
;; (trans target-1 target-2) -> (= X from to)
;; target-1 : (= X from middle)
;; target-2 : (= X middle to)
;; target-1: (= Nat (add1 (+ n-1 m)) (add1 (+ m n-1))
;; target-2: (= Nat (add1 (+ m n-1)) (+ m (add1 n-1))
;; result : (= Nat (add1 (+ n-1 m) (+ m (add1 n-1))
(define push-add1-trans
(lambda (n-1 m)
(lambda (1+n-1+m=1+m+n-1)
(trans 1+n-1+m=1+m+n-1 (1+n+m=n+m+1 m n-1)))))
;; final implementation of step-plus-comm
(define step-plus-comm
(lambda (m n-1)
(lambda (n-1+m=m+n-1)
(push-add1-trans n-1 m
(cong n-1+m=m+n-1 (+ 1))))))
(claim plus-comm
(Pi ((n Nat) (m Nat))
(= Nat (+ n m) (+ m n))))
(define plus-comm
(lambda (n m)
(ind-Nat n
(mot-plus-comm m)
(zero+=+zero m)
(step-plus-comm m))))